KOMUNIKASI LINTAS BUDAYA DALAM PROGRAM RELAWAN INTERNASIONAL: STUDI KASUS PROJECT WINGS SUMATRA - Bobby Caniago; Rezky Khoirina Tarihoran; Muhammad Danial (LPPI UMN AL WASHLIYAH, 2026)
Community service activities through international volunteer programs are one form of contextual learning that involves cross-cultural interaction. This article aims to describe cross-cultural communication practices in community service activities conducted at Project Wings Sumatra. The method used was a qualitative descriptive approach through direct observation, active participation, and documentation during the Field Work Practice (PKL) activities. The results indicate that interactions between local and international volunteers not only enhance English language communication skills but also foster an understanding of cultural differences, communication patterns, and social values. Furthermore, environmental education, waste management, and organic farming activities serve as effective platforms for strengthening cross-cultural communication in practical settings. These findings suggest that international volunteer-based service programs make a significant contribution to the development of students’ communication competencies and global awareness.